The Autophagy Receptor Adaptor p62 is Up‐regulated by UVA Radiation in Melanocytes and in Melanoma Cells2. (8th October 2017) - Sample, Ashley; Zhao, Baozhong; Wu, Chunli; Qian, Steven; Shi, Xianglin; Aplin, Andrew; He, Yu‐Ying
Abstract: UVA (315–400 nm) is the most abundant form of UV radiation in sunlight and indoor tanning beds. However, much remains to be understood about the regulation of the UVA damage response in melanocytes and melanoma. Here, we show that UVA, but not the shorter waveband UVB (280–315 nm), up‐regulates adaptor protein p62 in an Nrf2‐ and reactive oxygen species (ROS)‐dependent manner, suggesting a UVA‐specific effect on p62 regulation. UVA‐induced p62 up‐regulation was inhibited by a mitochondria‐targeted antioxidant or Nrf2 knockdown. In addition, p62 knockdown inhibited UVA‐induced ROS production and Nrf2 up‐regulation. We also report here a novel regulatory feedback loop between p62 and PTEN in melanoma cells. PTEN overexpression reduced p62 protein levels, and p62 knockdown increased PTEN protein levels. As compared with normal human skin, p62 was up‐regulated in human nevus, malignant melanoma and metastatic melanoma. Furthermore, p62 was up‐regulated in melanoma cells relative to normal human epidermal melanocytes, independent of their BRAF or NRAS mutation status. Our results demonstrated that UVA up‐regulates p62 and induces a p62‐Nrf2 positive feedback loop to counteract oxidative stress. Additionally, p62 forms a feedback loop with PTEN in melanoma cells, suggesting p62 functions as an oncogene in UVA‐associated melanoma development and progression. Abstract : UVA up‐regulates the autophagy adaptor protein p62 in epidermal melanocytes and melanoma cells. Up‐regulation of p62 requires reactive oxygen species (ROS) and Nrf2 activation, and p62 in turn promotes ROS generation and Nrf2 activation. Expression of p62 in melanoma cells also negatively regulates PTEN expression. Expression of PTEN in melanoma is sufficient to reduce p62 expression, creating a regulatory feedback loop.